A new fan-like adaptive porous organic cage for the structure determination of liquid perfume molecules. Issue 5 (14th February 2023) - Zhou, Yu; Luo, Peng; Xu, Li-Jun; Xu, Wei; Jiang, Ren-Wang
Abstract : Chloroform and nine liquid perfume guests were successfully encapsulated by a newly synthesized fan-like adaptive porous organic cage. Abstract : A new fan-like adaptive porous organic cage (FPOC) was synthesized for the structure determination of liquid perfume molecules. The FPOC was used as a molecule catcher because (i) it contains extrinsic cavities in the network; (ii) the CN moiety can be used as the hydrogen bond acceptor, and the numerous hydrocarbons can be used as hydrogen bond donors; and (iii) the rich benzene rings can form aromatic interactions. The liquid perfume guests 1–9 [ N, N -diethyl-3-methylbenzamide (1 ), 1, 3-dimethoxybenzene (2 ), toluene (3 ), eugenyl acetate (4 ), ( E )-methyl isoeugenol (5 ), ( R )-carvone (6 ), ( S )-carvone (7 ), trans -anethole (8 ) and 1, 8-cineole (9 )] are successfully encapsulated in the extrinsic cavity of the FPOC and ten new crystals were obtained (including the cage). Theoretical calculations using Multiwfn software showed that the guest volumes were found to be in a wide range from 180.189–661.027 Å 3, indicating that the FPOC was guest adaptive. To the best of our knowledge, this is the first report on the encapsulation properties between an adaptive porous organic cage and liquid perfume molecules. All guests form C–H⋯π or C–H⋯O interactions with the FPOC, highlighting the important role of weak interactions in the structure determination of liquid perfume molecules.